La disponibilité temporelle au travail des femmes : une disponibilité sans contrepartie ? - François-Xavier Devetter (Temporalités)
This article uses a broader concept of working time than mere duration (time availability at work encompassing the volume of hours worked but also the scheduling and predictability of those hours), to examine the gender gap concerning temporal constraints. Women seem to dispose of fewer possibilities to make themselves available at work than men but, more importantly, this gap does not involve the same aspects of time. The temporal constraints experienced mainly by women are less socially visible and hence undervalued by their employers.